A Favorable Legal Environment for Voucher Programs - Chopko, Mark E. (Catholic Education: A Journal of Inquiry and Practice, 1999)
A pressing legal issue at the close of the millennium is the use of public tax dollars to assist parents, especially lower income parents, with the rising tuition at private schools. The idea of vouchers, as they have been commonly named, has been argued in legal circles for decades. However, the 1990s have seen a particular urgency on this issue as several states have passed legislation implementing pilot programs. This article summarizes the current state of the debate, reviews significant legal cases, and highlights the differences among individual states in their interpretation and application of the law. While maintaining that a properly designed voucher program could pass constitutional review by the U.S. Supreme Court, the author argues that broader public policy and justice issues are at stake.